The Working Range of Vibrational Conveyers with Nonideal Vibration Exciter: Primary Resonance - Alisverisci, G. F.; Bayiroglu, H.; Unal, G. (TECHNICAL UNIVERSITY LIBEREC, 2011)
Vibrational conveyers with a centrifugal vibration exciter transmit their load based on the jumping method. The trough is oscillated by a common unbalanced-mass driver. This vibration causes the load to move forward and upward. The movement is strictly related to the vibrational parameters. The transition over resonance of a vibratory system, excited by rotating unbalances, is important in terms of the maximum vibrational amplitude produced and the power demand on the drive for the cross-over. The mechanical system depends on the motion of the DC motor. In this study, the working ranges of oscillating shaking conveyers with nonideal vibration exciter have been analyzed analytically for primary resonance by the Method of Multiple Scales with Reconstitution, and numerically. The analytical results obtained in this study have been compared with the numerical results, and have been found to be well matched.
Keywords: Centrifugal vibration exciter; vibrational conveyers; nonideal vibrations; The Method of Multiple Scales with Reconstitution; primary resonance; TRANSITION; Engineering